Cold start particle number, size and mass emissions from a CRDI diesel engine running on biodiesel blends in a cold environment. Issue 4 (3rd July 2016) - Ramadhas, Arumugam Sakunthalai; Xu, Hongming
ABSTRACT: Biodiesel is a renewable alternative fuel, used as a blending component for diesel, which reduces hydrocarbon and particulate matter emissions with marginal increases in nitrogen oxide emissions. Engine performance varies with ambient temperature conditions, engine design, fuel, lubricant and operating conditions. This research investigated the impact of biodiesel blends on a common rail direct injection (CRDI) diesel engine performance and exhaust emission characteristics during cold start at different ambient temperature conditions. Biodiesel blends improved the combustion and thereby reduced the sudden rise in peak speed and the gaseous emissions at normal ambient temperature. At cold ambient conditions biodiesel severely affected the cold start performance and increased the gaseous emissions. During cold start, the biodiesel blends emitted a larger number of particles of diameter 100–1000 nm at cold ambient temperature compared to normal ambient temperature. The particulate surface area and mass was increased by 2–3 times and 3–6 times, respectively, for the biodiesel blends with the drop in ambient temperature. The higher number of larger diameter particles increased the particulate mass significantly at cold ambient temperature conditions.